Analisis Kemampuan TPACK (Technological, Pedagogical, and Content Knowledge) Guru Matematika melalui Rencana Pelaksanaan Pembelajaran - Rahma, Fatikh Inayahtur; Yumnah, Siti; Rokim, Rokim (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2024)
This research aims to describe two things: (1) the contents of the RPP; and (2) teachers' technology pedagogy content knowledge (TPACK). Furthermore, this research uses triangulation of methods and sources to ensure the accuracy of the information. The research findings show that: (1) SDI teacher Wahid Hasyim already knows TPACK and knows how to use technology even though initially it was not perfect and needed improvement to meet students' learning needs. Furthermore, research has shown that educators can effectively integrate the use of technology, various techniques, and various learning methodologies when creating their plans for implementing learning. Despite this, the TPACK RPP content is excellent.